1020. Higher efavirenz mid-dose plasma concentration is associated with less weight gain among virologically suppressed people living with HIV. (31st December 2020) - Huang, Wei-chieh; Huang, Sung-Hsi; Hung, Chien-Ching
Abstract: Background: Recently, an association between CYP2B6 516 G > T polymorphism and weight change was observed among African people living with HIV (PLWH) who were started on efavirenz(EFV)-based antiretroviral therapy (ART). We aimed to investigate the effect of EFV mid-dose plasma concentration on weight change among Taiwanese PLWH. Methods: The medical records of adult PLWH who were taking EFV-containing ART and had been enrolled in a EFV therapeutic drug monitoring study between Oct 2009 and May 2014 were accessed. EFV mid-dose plasma concentration (C12) was determined in the previous study and those with serial weight measurements within 48 weeks around the time of EFV C12 measurement were included in the present study. The weight change in the 48 weeks and its associations with mid-dose EFV concentrations and CYP2B6 516 G > T polymorphism were examined by general estimating equations (GEE) after adjusting for age, baseline HIV viremia, baseline weight, and the companion backbone antiretroviral agents. Results: One-hundred and fifteen predominantly male (94.8%) PLWH were included in this study (Table 1). The mean CD4 lymphocyte count was 542 cells/μL at the beginning of the observation and 94.8% achieved HIV viral suppression. Forty-four (38.3%) patients had non-wildtype CYP2B6 516 G > T polymorphism. On average, the included PLWH gained 0.8 kilogram at 48 weeks and the weight change did not differ among those with wildtype and non-wildtype CYP2B6 516 G > T(Figure 1). In the GEE models, CYP2B6 516 G > T polymorphism was not associated with weight change (p=0.81), instead, higher EFV C12 was found to be independently associated with less weight gain (p=0.045). Table 1. Baseline characteristics. Figure 1. The absolute weight (A) and weight change from baseline (B) among patients with wildtype and non-wildtype CYP2B6 516G>T polymorphism. Conclusion: Our findings support that increased EFV exposure may have a negative effect on weight gain. Disclosures: Chien-Ching Hung, MD, PHD, Abbvie (Advisor or Review Panel member, Speaker's Bureau)Bristol-Myers Squibb (Speaker's Bureau)Gilead Sciences (Advisor or Review Panel member, Speaker's Bureau)Janssen (Grant/Research Support, Advisor or Review Panel member)Merck (Grant/Research Support)ViiV (Grant/Research Support, Advisor or Review Panel member, Speaker's Bureau)